Q&A: Trends in agricultural extension and ICTs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Agricultural extension finds itself at a time of crisis. Many of today´s agricultural extension services are suffering under bureaucratic centralized management structures.